Alteration by heat shock and immunological characterization of Drosophila small nuclear ribonucleoproteins (The Rockefeller University Press, 1989)
Sera from human patients with systemic lupus erythematosus (SLE) have been shown to react with snRNP particles of both mammals and Drosophila (Mount, S. M. and J. A. Steitz. 1981. Nucleic Acids Res. 9:6351-6368). We have utilized fully characterized monospecific sera and specifically purified antibodies to carry out indirect immunofluorescence experiments with frozen sections of Drosophila embryos. Embryos subjected to severe heat shock before sectioning showed reduced binding of anti-Sm sera. Anti-nRNP sera reacted identically with antigens of heat shocked and non-heat-shocked sections. The reduction in anti-Sm fluorescence was restored by a brief salt wash. These results imply a noncovalent alteration in the conformation of Sm antigens with the administration of heat shock that can revert with exposure to salt. Drosophila antigens have been compared to mammalian standards, showing partial identity with bovine spleen extract (BSE) antigens when reacted with anti-Sm sera. The antigenic relatedness between affinity-purified heat-shocked and non-heat-shocked Drosophila antigens and their mammalian homologues was examined by quantitative ELISA methodology. In all cases, the Drosophila antigens from heat-shocked and non-heat- shocked embryos were identical. We theorize that the heat shock-induced alteration of Sm antigen reverst during extraction. Because the snRNP antigens have been shown to be involved in splicing, and because splicing is inhibited during heat shock (Yost, H. J., and S. Lindquist. 1986. Cell. 45:185-193), our results provide information on the nature and stability of a change in these antigens which may be a central element in control of the heat shock response.